Histopathological Transformation in Medullary Thyroid Carcinoma (MTC) With Poorly Differentiated Thyroid Carcinoma (PDTC): a Case Study of Aggressive Thyroid Cancer in An 18-Year-Old Female - Jamnasi, Juli; Bangun, Jonas A.; Tambunan, Ronald T. H.; Mega, Juli Yosa; Lumban Tobing, Paul S.; Fauzi, Tengku M. (Universitas Methodist Indonesia, 2025)
Medullary Thyroid Carcinoma (MTC) is a type of thyroid cancer originating from C cells, while Poorly Differentiated Thyroid Carcinoma (PDTC) is a more aggressive form with poor differentiation. The transformation between these two types can affect prognosis and treatment strategies. This study analyzes an 18-year-old female patient presenting with neck swelling and difficulty swallowing. The initial diagnosis of MTC was established through fine-needle aspiration biopsy (FNAB), and after surgical resection, histopathological analysis was conducted to evaluate any transformation to PDTC. Histopathological findings revealed MTC areas with high calcitonin-producing C cells. However, there were also areas exhibiting characteristics of PDTC, including increased mitotic activity, necrosis, and loss of calcitonin expression. This transformation indicates a shift from a more indolent cancer form to a more aggressive one. The transformation from MTC to PDTC in a young patient underscores the importance of careful monitoring and thorough histopathological evaluation. Appropriate management and understanding of these changes are crucial for improving treatment outcomes. Further studies are needed to elucidate the molecular mechanisms underlying this transformation.